An Empirical Study on Perception and Behaviour of Investors towards Equity Market Investments - Dr. A. Sree Ram, Ms.Gopisetty Reshma, Dr. K. Raghuveer, Dr. B. Hari Babu (Journal of Informatics Education and Research, 2024)
Perception and Behaviour of Investors' towards the performance of equity indices in the stock market were meticulously examined in this study. By delving into their perceptions, we aim to provide valuable insights to help investors make informed decisions that lead to financial success. As part of a research study, the required data has been gathered from 415 individuals who invest in the equity market. The study aimed to investigate how investors' decision-making behavior, whether rational or irrational, affects their perceptions of movements in equity stock indices. The data was analyzed using the Structural Equation Model approach. The study revealed that the model had an excellent fit to the suggested values, indicating that investors use both rational and irrational approaches in their investment decision-making process. Although they collect complete financial information, they also use shortcuts to make investment decisions.